Inducing mitophagy in diabetic platelets protects against severe oxidative stress - Seung Hee Lee; Jing Du; Jeremiah Stitham; Gourg Atteya; Suho Lee; Yaozu Xiang; Dandan Wang; Yu Jin; Kristen L Leslie; Geralyn Spollett; Anup Srivastava; Praveen Mannam; et al. (EMBO Molecular Medicine, 2016)
Abstract Diabetes mellitus (DM) is a growing international concern. Considerable mortality and morbidity associated with diabetes mellitus arise predominantly from thrombotic cardiovascular events. Oxidative stress‐mediated mitochondrial damage contributes significantly to enhanced thrombosis in DM. A basal autophagy process has recently been described as playing an important role in normal platelet activation. We now report a substantial mitophagy induction (above basal autophagy levels) in diabetic platelets, suggesting alternative roles for autophagy in platelet pathology. Using a combination of molecular, biochemical, and imaging studies on human DM platelets, we report that platelet mitophagy induction serves as a platelet protective mechanism that responds to oxidative stress through JNK activation. By removing damaged mitochondria (mitophagy), phosphorylated p53 is reduced, preventing progression to apoptosis, and preserving platelet function. The absence of mitophagy in DM platelets results in failure to protect against oxidative stress, leading to increased thrombosis. Surprisingly, this removal of damaged mitochondria does not require contributions from transcription, as platelets lack a nucleus. The considerable energy and resources expended in “prepackaging” the complex mitophagy machinery in a short‐lived normal platelet support a critical role, in anticipation of exposure to oxidative stress.